KOMUNIKASI PEMASARAN TRANSITORY COFFEE DEPOK DI MASA PANDEMI COVID-19 - Wardhani, Firda Kusuma (Jurnal Insani, 2023)
Marketing communication is a form of communication that aims to help strengthen the marketing strategy of a company or a business. Marketing communication can also be interpreted as an activity that aims to introduce, establish relationships between companies and company partners, both suppliers and consumers. Things that are introduced and communicated to outsiders are about the products and services offered by the company, so it can be said that marketing communication is the key for companies to achieve the success of their business objectives, especially in the era of the Covid 19 Pandemic. This research will discuss how Transitory Coffee Depok carries out its marketing communication strategy. The object of this research is located in Depok, West Java in pandemic era. This research used a descriptive qualitative type where the author goes directly to the field and conducts interviews with the informants. Based on the results of the analysis carried out, it can be concluded that Marketing Communication at the Transitory Coffee Depok uses marketing sales, personal selling, marketing events, advertising, and media publications that are often used are Instagram and Tiktok.